2018
DOI: 10.1055/s-0044-100042
|View full text |Cite
|
Sign up to set email alerts
|

Getting More Than You Paid For: Unauthorized “Natural” Substances in Herbal Food Supplements on EU Market

Abstract: As the population in the industrialized world develops preference for what is perceived as a natural and holistic way of disease treatment, the popularity and the number of food supplements on the market, including herbal ones, is experiencing an unprecedented rise. However, unlike herbal medicinal products, intended for treating or preventing disease, current legislation classifies food supplements as products intended for achieving nutritional or physiological effect and to supplement the normal diet. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 122 publications
(192 reference statements)
0
16
0
Order By: Relevance
“…At the international level, the regulation is fragmented and varies between markets, the European Food Safety Authority’s (EFSA) Nutrition and Health Claims Regulation (NHCR) being one of the strictest [34]. The availability of cheap and counterfeit products challenges the industry, especially in developing markets [23] but illegal ingredients such as those banned by the World Anti-Doping Agency (WADA) have been found worldwide (see e.g., references [35,36,37]). Marketing of supplements for extending beyond sportsmen has increased ethical concerns [38,39].…”
Section: Consumption and Trends In Food And Supplements Intended Fmentioning
confidence: 99%
“…At the international level, the regulation is fragmented and varies between markets, the European Food Safety Authority’s (EFSA) Nutrition and Health Claims Regulation (NHCR) being one of the strictest [34]. The availability of cheap and counterfeit products challenges the industry, especially in developing markets [23] but illegal ingredients such as those banned by the World Anti-Doping Agency (WADA) have been found worldwide (see e.g., references [35,36,37]). Marketing of supplements for extending beyond sportsmen has increased ethical concerns [38,39].…”
Section: Consumption and Trends In Food And Supplements Intended Fmentioning
confidence: 99%
“…Herbal supplements, which are commonly perceived by patients as completely safe due to their natural origin, are particularly dangerous [102][103][104]. The risk is associated, among others, with the higher content of active substances in the supplements than occur in the natural herbal resources, which results from the use of concentrated extracts and sometimes additional synthetic analogues [105,106]. Additionally, recent years have witnessed the appearance of numerous preparations that include plants that have never previously been used in Western medicine.…”
Section: Cancer Therapymentioning
confidence: 99%
“…There is also an associated problem of additional ingredients that are also dangerous being included with the banned substances. For instance, the number of reports on laxatives, antidepressant, yohimbine, and even amphetamine and its derivatives being found in supplements continues to grow [105,106,127,137]. A US study revealed that 11 out of 21 supplements that contained the Acacia rigidula extract that were purchased on the Internet contained the isomer of amphetamine [138].…”
Section: Safety Of Supplement Usementioning
confidence: 99%
See 2 more Smart Citations